2016
DOI: 10.1158/1055-9965.epi-15-0876
|View full text |Cite
|
Sign up to set email alerts
|

Racial Differences in the Association Between Preoperative Serum Cholesterol and Prostate Cancer Recurrence: Results from the SEARCH Database

Abstract: Background Black men are disproportionately affected by both cardiovascular disease and prostate cancer. Epidemiologic evidence linking dyslipidemia, an established cardiovascular risk factor, and prostate cancer progression is mixed. As existing studies were conducted in predominantly non-black populations, research in black men is lacking. Methods We identified 628 black and 1,020 non-black men who underwent radical prostatectomy and never used statins before surgery in the Shared Equal Access Regional Can… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 31 publications
2
16
0
Order By: Relevance
“…Biochemical, cellular and molecular factors may promote cancer growth and metastasis among African American women (35,36). In addition, altered metabolic and inflammatory profile might be involved in the high prevalence rates of comorbid conditions (e.g., obesity, diabetes or chronic stress) and adverse cancer outcomes in African Americans (37)(38)(39)(40)(41). A better understanding of racial/ethnic differences in de novo metastases sites and survival outcomes is required.…”
Section: Discussionmentioning
confidence: 99%
“…Biochemical, cellular and molecular factors may promote cancer growth and metastasis among African American women (35,36). In addition, altered metabolic and inflammatory profile might be involved in the high prevalence rates of comorbid conditions (e.g., obesity, diabetes or chronic stress) and adverse cancer outcomes in African Americans (37)(38)(39)(40)(41). A better understanding of racial/ethnic differences in de novo metastases sites and survival outcomes is required.…”
Section: Discussionmentioning
confidence: 99%
“…The study found that while obesity was associated with a 46% lower likelihood ( p = 0.02) of having abnormal PSA among white men, obesity was linked to a higher likelihood of having abnormal PSA among black men, although this association was not significant ( p = 0.11) [12]. Finally, three other studies deserve mention [1315]. Before discussing the papers, it is important to note that all three studies included men with prostate cancer and examined predictors of either high-grade disease [14] or recurrence after surgery [13,15] as opposed to the studies discussed above, which focused on predictors of having versus not having prostate cancer.…”
Section: Evidence Synthesismentioning
confidence: 99%
“…Finally, three other studies deserve mention [1315]. Before discussing the papers, it is important to note that all three studies included men with prostate cancer and examined predictors of either high-grade disease [14] or recurrence after surgery [13,15] as opposed to the studies discussed above, which focused on predictors of having versus not having prostate cancer. Despite these differences in study design, all the studies found either obesity itself or factors correlated with obesity (visceral fat and serum cholesterol) were only correlated with aggressive prostate cancer in black men and not white men.…”
Section: Evidence Synthesismentioning
confidence: 99%
“…The study by Allott et al (2016)9 assessed the association between serum cholesterol and prostate cancer recurrence in black and non-black men separately, which was considered as two independent studies. Risk estimates and their corresponding 95% CIs were not directly available in the study by Ohno et al,17 which were calculated from the data reported in the articles using the methods proposed by Parmar et al18…”
Section: Methodsmentioning
confidence: 99%
“…The impact of dyslipidemia on the risk of prostate cancer recurrence has been evaluated by various epidemiologic studies. Some studies reported positive associations between elevated cholesterol,9 low-density lipoprotein (LDL),10 or triglyceride9 and the risk of prostate cancer recurrence, while others reported no associations11,12 or even inverse associations 1315. Therefore, we aimed to investigate the effects of serum lipid levels, including total cholesterol, LDL, high-density lipoprotein (HDL), and triglyceride, on the prostate cancer recurrence after radical prostatectomy based on a meta-analysis of all eligible studies.…”
Section: Introductionmentioning
confidence: 99%